HUMOR ANALYSIS IN ASTERIX AT THE OLYMPIC GAMES COMIC - Shalihah, Miftahush (Lire Journal (Journal of Linguistics and Literature), 2022)
Humor can be found in both spoken and written language, which is an imitation of spoken language. Comic books are one type of written source of humor. Asterix at the Olympic Games is one of comic which contains humor. The purpose of this paper is to determine how linguistic context and non-linguistic context produce humor in the comic Asterix at the Olympic Games. This study used a descriptive qualitative approach. The study's findings revealed that speech acts and maxims violations were linguistic contexts that contributed to the production of humor. Character expression and illustration, on the other hand, contributed to the production of humor in a non-linguistic context.